Taxpayer's Interest in Using Tax Consultant Services - Novalia, Nafisah; Masitoh, Endang; Siddi, Purnama (JIFA (Journal of Islamic Finance and Accounting), 2021)
This study aims to obtain empirical evidence to determine the effect of knowledge, perceptions of tax consultants, tax sanctions, and taxpayer motivation on interest in using tax consultant services. The independent variables in this study are knowledge, perceptions of tax consultants, tax sanctions, and taxpayer motivation. The dependent variable in this study is the interest in using the services of a tax consultant. The data in this study are primary data obtained from a questionnaire sample of 83 individual taxpayers in the Solo Raya area, using purposive sampling method. The data analysis technique used multiple linear, the data was processed using SPSS 22. The results of the analysis showed that the perception of tax consultants, tax sanctions, and taxpayer motivation had a positive effect on interest in using tax consultant services. Knowledge has a negative effect on interest in using the services of a tax consultant.